A framework of interactive mind-map multimedia system in blended learning / Chen Xinyu and Prof. Dr. Wan Ahmad Jaafar Wan Yahaya - Chen, Xinyu; Wan Yahaya, Wan Ahmad Jaafar (Universiti Teknologi MARA, Kedah, 2023)
In modern education, students advocate a high-quality and intelligent instructional environment, and their requirements have changed in lockstep, including how they participate in the classroom, acquire knowledge, improve innovation, and confidently solve problems. In the target group involved in this study, the students from the design colleges tend to stay in mastering design skills and lack innovation. They have a certain level of artistic thinking but are often not competent in the thinking ability to complete the user-centered functions and services of the whole application required. Thus, conventional instructional design and thinking are facing an awkward position, while blended learning will play the future instructional design role in the next normal. The framework of interactive and mind-map multimedia systems is one of the manifestations of blended learning that may change this embarrassing situation. Therefore, the research purpose is to design an interactive and mind-map multimedia instructional system for enhancing Chinese design college students’ innovation and service design thinking.